Theoretical kinetic study of the reaction of SF5 radical with F2, Cl2 and SF5 - Buendia Atencio, Cristian Ignacio (2016)
A kinetic study of the gas phase reaction of the SF5 radical with the species F2, Cl2 and SF5 has been performed. Quantum chemical calculations employing the DFT methods B3LYP, BMK, MPWB1K, BB1K and M06-2X combined with the 6-311+G(3df) basis set provide the required relevant parts of the potential energy surfaces. Transition state theory calculations for the SF5 + F2 → SF6 + F reaction lead to the rate coefficient 1.4 × 10-12 exp(-4.1 kcal mol-1/RT) cm3 molecule-1 s-1 at 213-245 K. From similar calculations, the expression 2.1 × 10-11 exp(-7.6 kcal mol-1/RT) cm3 molecule-1 s-1 was obtained for SF5 + Cl2 → SF5Cl + Cl. The combination of the rate coefficients obtained for the F atom abstraction reaction with reported experimental kinetic information yields the value 3 × 10-12 cm3 molecule-1 s-1 for the SF5 + SF5 → S2F10 association reaction. A comparison with SACM/CT calculations and previous conflicting rate coefficients for this process is presented.